Evaluation of polyamidoamine dendrimers as potential carriers for quercetin, a versatile flavonoid. (2nd January 2016) - Madaan, Kanika; Lather, Viney; Pandita, Deepti
Abstract: The aim of the present research work was to investigate the potential of polyamidoamine (PAMAM) dendrimers as oral drug delivery carriers for quercetin, a Biopharmaceutical Classification System (BCS) class II molecule. The aqueous solubility of quercetin was investigated in different generations of dendrimers, i.e. G0, G1, G2 and G3, with varying concentrations (0.1, 0.5, 1, 2 and 4 µM). Then, it was successfully incorporated in PAMAM dendrimers and they were characterized for incorporation efficacy, nature of nanoformulations, size, size distribution, surface morphology and stability. In vitro release characteristics of quercetin from all quercetin-PAMAM complexes were studied at 37 °C in phosphate buffer saline (PBS; pH 7.4). Furthermore, the efficacy of quercetin-loaded PAMAM dendrimer was assessed by pharmacodynamic experiment, namely, a carrageenan-induced paw edema model to evaluate the acute activity of this nanocarrier in response to inflammation. It was observed that both generation and the respective concentrations of PAMAM dendrimers showed potential positive effects on solubility enhancement of quercetin. All the quercetin-PAMAM complexes were found to be in nanometeric range (<100 nm) with narrow polydispersity index. In vitro study revealed a biphasic release pattern of quercetin which was characterized by an initial faster release followed by sustained release phase and pharmacodynamic study provided the preliminary proof of concept about the potential of quercetin-PAMAM complexes. The study concludes that the dendrimer-based drug delivery system for quercetin has enormous potential to resolve the drug delivery issues associated with it.